2021
DOI: 10.1177/00220345211019922
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Socket Repair via WNT3A Curtails Alveolar Ridge Resorption

Abstract: Tooth extraction triggers alveolar ridge resorption, and when this resorption is extensive, it can complicate subsequent reconstructive procedures that use dental implants. Clinical data demonstrate that the most significant dimensional changes in the ridge occur soon after tooth extraction. Here, we sought to understand whether a correlation existed between the rate at which an extraction socket heals and the extent of alveolar ridge resorption. Maxillary molars were extracted from young and osteoporotic rode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The importance of space maintenance for bone regeneration has been proposed in guided bone regeneration (Briguglio et al, 2019). Recently, Arioka et al (2022)demonstrated a causal link between enhancing socket repair and preserving alveolar ridge dimensions following tooth extraction. Hence, RBM may have promoted bone regeneration in the extraction socket, which may also have contributed to the space maintenance and suppressed alveolar ridge absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of space maintenance for bone regeneration has been proposed in guided bone regeneration (Briguglio et al, 2019). Recently, Arioka et al (2022)demonstrated a causal link between enhancing socket repair and preserving alveolar ridge dimensions following tooth extraction. Hence, RBM may have promoted bone regeneration in the extraction socket, which may also have contributed to the space maintenance and suppressed alveolar ridge absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Schropp et al reported that, in most cases in humans, decreases in alveolar bone height and width both occurred immediately after extraction [7]. According to Arioka et al, alveolar bone resorption also occurs immediately after tooth extraction in rodents [29], and RP is considered to be effective for protection of the alveolar ridge after tooth extraction. In the present study, the post-extraction alveolar bone resorption rate was lower in both groups that underwent RP than in the CTL group, with the reduction in width in particular being signi cantly lower, demonstrating the effectiveness of RP.…”
Section: Discussionmentioning
confidence: 99%
“…Lineage tracing has also been used to investigate the osteogenic potential of periodontal cell populations in tooth extraction sites. Wnt-responsive cells, indicated by expression of Axin2, were present in small numbers in healthy periodontal tissues (70,71). After tooth extraction, Axin2-lineage cells that remained in the residual PDL proliferated and migrated into the socket.…”
Section: Periodontal Progenitor Cellsmentioning
confidence: 99%